2009
DOI: 10.1021/jz900173w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Salt Rejection in Model Surface-Modified Nanopores

Abstract: This Letter describes molecular dynamics simulations of pressureinduced flow of water and aqueous salt solutions through model nanopores. The systems studied are comprised of (n,n) carbon nanotubes (CNT) that span a membrane constructed of parallel graphene walls separating two solution reservoirs. We employ this system as an idealized model of surface-modified nanoporous membranes, and thus, both native hydrophobic CNT and nanotubes with artificial surface partial charge patterns are considered. The dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 43 publications
4
61
0
Order By: Relevance
“…This result was significant for the specific functionalization of CNTs with small diameter since the presence of charged functional groups on the CNT tip may enable them to control the ionic flow and the exclusion of very small ions. Goldsmith and Martens have also provided some suggestion to improve the ion rejection, in which they ascribed this original mechanism to both direct electrostatic interactions between the charges of CNTs surface and the solution ions and the incidental impact of the water structuring induced by various charge patterns (Goldsmith and Martens 2009). The interfacial friction of water was also studied on graphitic interfaces with different topologies, including the water molecules between the graphene sheets, inside and outside the pores of CNTs (see Fig.…”
Section: Separation Of Gaseous Mixtures Using Cnt Bundlesmentioning
confidence: 99%
“…This result was significant for the specific functionalization of CNTs with small diameter since the presence of charged functional groups on the CNT tip may enable them to control the ionic flow and the exclusion of very small ions. Goldsmith and Martens have also provided some suggestion to improve the ion rejection, in which they ascribed this original mechanism to both direct electrostatic interactions between the charges of CNTs surface and the solution ions and the incidental impact of the water structuring induced by various charge patterns (Goldsmith and Martens 2009). The interfacial friction of water was also studied on graphitic interfaces with different topologies, including the water molecules between the graphene sheets, inside and outside the pores of CNTs (see Fig.…”
Section: Separation Of Gaseous Mixtures Using Cnt Bundlesmentioning
confidence: 99%
“…Indeed, it offers unique opportunities to connect some macroscopic properties to a microscopic description of the physical phenomena involved in the separation. Although MD has been already applied to investigate both water and ion transports through nanopores with well-defined geometries [12][13][14][15][16][17][18], the limited information about the three-dimensional molecular structure of RO polyamide membranes makes the use of this computational method much more challenging. As a result, the identification and the understanding at a microscopic level of the underlying mechanisms governing water and ion transport through RO membranes are proceeding very slowly and only few studies reported on the attempt of building full atomistic models of RO polyamide membranes [19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…1(a)]. The hydrophobic region of the pattern is a solid surface without charge, and the atoms in this solid surface have the same Lennard-Jones parameters as the carbon in graphite [36,37]. Graphite is usually regarded as hydrophobic [38], and simulations show that water has a contact angle near 50°[ Fig.…”
mentioning
confidence: 99%